2019
DOI: 10.1111/apt.15132
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B is associated with an increased risk of B‐cell non‐Hodgkin's lymphoma and multiple myeloma

Abstract: Background: Chronic hepatitis B has been linked to lymphoma with contradictory results.Aim: To investigate the association between chronic hepatitis B and lymphoma by using a nationwide population-based cohort. Methods: Records of patients diagnosed with chronic hepatitis B (hepatitis B virus[HBV] cohort) or without (non-HBV cohort) during 2004-2007 were retrieved from the Taiwan National Health Insurance Research Database. Age, sex, comorbidities, and medical visits were matched using propensity scores betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
0
30
1
Order By: Relevance
“…CHB has also been associated with a higher prevalence of malignancy, including colorectal, pancreatic, gallbladder and biliary duct, kidney, and ovarian cancer, as well as Hodgkin's lymphoma, non‐Hodgkin's lymphoma, and multiple myeloma . There has been some debate regarding the association of CHB and lymphoma .…”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 99%
See 3 more Smart Citations
“…CHB has also been associated with a higher prevalence of malignancy, including colorectal, pancreatic, gallbladder and biliary duct, kidney, and ovarian cancer, as well as Hodgkin's lymphoma, non‐Hodgkin's lymphoma, and multiple myeloma . There has been some debate regarding the association of CHB and lymphoma .…”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 99%
“…However, in 2002, Kim et al performed a case‐control study in Korea and found that the risk for B cell non‐Hodgkin's lymphoma was increased among patients with CHB, with an adjusted odds ratio (OR) of 3.30 (95% CI: 1.69‐6.45). Further, in a claims‐based study conducted in Taiwan comparing patients with CHB against those without, Su et al found HBV to be a risk factor for both lymphoma (hazard ratio [HR] 2.07 [95% CI: 1.76‐2.43]) and non‐Hodgkin's lymphoma (HR 2.18 [95% CI: 1.80‐2.65]), as well as for multiple myeloma. Several other studies have also corroborated the finding that CHB is linked to development of lymphoma .…”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the recent large-scale cohort study by Su et al 1 reporting that chronic hepatitis B virus (HBV) infection is an independent risk factor for multiple myeloma (MM) (hazard ratio:…”
Section: Letter: Hepatitis B Virus Infection and Risk Of Multiple Myementioning
confidence: 99%